Linkage between Right to Development and Rights-based Approach: An Overview (Northern University Journal of Law, 2014)
The concept of right to development has been inserted into the rights discourse quite recently, though it was known earlier that theg proper implementations of human rights tend to secure the life standard and progressive development of the community. New concepts of development expressed its concern for the overall betterment of human being.1 Right to Development (RTD) is being recognized as a collective right in the human rights arena. On the other hand, Rights Based Approach (RBA) has an inseparable link with right to development which seeks for the identification of issues to make a need based assessment. In brief, a human-rights approach translates poor peoples needs into rights, and recognizes individuals as active subjects and stakeholders. It further identifies the obligations of states that are required to take steps for example through legislation, policies and programs with a view to respect, promote and fulfill the human rights of all people within their jurisdiction.2 RBA addresses rights based issue to achieve goals adopted by MDG, like alleviating poverty, promoting education, ensuring gender equality and empowerment of the women, developing a global partnership for development etc. In this article, the right to development is being tried to accurately affiliate with the framework known as Rights Based Model with a view to characterizing a successful coordination between the two. Thus if the states intend to adjust their methods of functioning and fulfill their obligations to the beneficiaries according to the rights based model, the recognized human rights such as economic, social, cultural rights involved in human development would be enjoyed and respected by an individual irrespective of his class, group, origin and any other attributes. DOI: http://dx.doi.org/10.3329/nujl.v1i0.18528 Northern University Journal of Law Vol.1 2010: 96-111